The Accuracy of ChatGPT in Translating Colloquial Terms in Dawan Language - Iis Aprianti; Yoni Rahayu; Soraya Grabiella Dinamika; Muhammad Muslim Nasution (Faculty of Education and Teacher Training of UIN Palopo, 2025)
ChatGPT, a multilingual translation application has made intercultural conversation simpler including local language. However, ChatGPT's translation accuracy should be reviewed due to limits in recognizing domain-specific terms and cultural context. The aim of this study is to find out the translation accuracy of ChatGPT in translating colloquial terms in Dawan language. This study used qualitative method. The participants of this study were from the sixth semester English department students of University of Timor. The data source of this study was the translation result in Dawan into Indonesian language. While, the data of this study are ChatGPT’s translation result obtained from students’ word list from Dawan into Indonesian language. The result of the analysis showed showed that ChatGPT performs relatively well in translating basic vocabulary and common expressions, with 60% of the translations deemed accurate. However, the tool demonstrated significant limitations in handling culturally embedded and context-dependent terms.